Paradoxical air embolism and neurological insult during removal of a pulmonary artery catheter introducer. (10th July 2014) - Bowles, Philippe Frederick; Lear, Christopher; Maccario, Marco; Kong, Robert
Abstract : A 54-year-old man was admitted to the intensive care unit following cardiac surgery. On day 6 postoperatively, approximately 2–3 min following the removal of the pulmonary artery (PA) catheter introducer sited in the right internal jugular vein, the patient became agitated, confused and then unresponsive. He was urgently moved onto the bed, laid supine, sedated with a propofol infusion, intubated and mechanically ventilated. A bedside transthoracic echocardiogram revealed extensive multiple air emboli in all cardiac chambers and review of the patient's intraoperative imaging confirmed the presence of patent foramen ovale (PFO). The following morning, sedation was discontinued and the trachea extubated. The patient was later transferred to the ward and then discharged home with no evidence of neurological deficit. This case reminds us of the importance of strict adherence to safety protocols when manipulating centrally positioned catheters and the high prevalence of undiagnosed PFO.